Directive Functions of The Letters of Prophet Muhammad Pbuh for The Kings and The Warlords - L-Islami, CA Bunia; Rustono, Rustono; Haryadi, Haryadi (Universitas Negeri Semarang, 2021)
The best figure along the history of mankid in life namely Prophet Muhammad PBUH had good diction, gentle language style, firm commands and prohibitions. In addition, he also selected carefully the messengers who had good faith and morals. The purpose of this study is to describe the type, function, and effect of directive utterances in several letters of the Prophet Muhammad to his kings and commander. This research uses a theoretical and methodological approach. The data collection method in this study is a free and involved method and note taking technique. The use of data analysis methods in this study is a heuristic and normative method. Researchers use the method of presenting the analysis an informal result. The results of this study are the function of directive speech includes praying, directing, granting, ordering, requiring, prohibiting, and require. The benefit is to know the grammar of writing from the prophet to regional officials and how to treat his letters.